Different Effects of Startling Acoustic Stimuli (SAS) on TMS-Induced Responses at Rest and during Sustained Voluntary Contraction - Chen, Yen-Ting; Li, Shengai; Zhou, Ping; Li, Sheng (Frontiers in Human Neuroscience, 2016)
A conditioning startling acoustic stimulus (SAS) can cause transient suppression of transcranial magnetic stimulus (TMS)-induced motor evoked potential (MEP) at rest. However, it is still unknown whether this phenomenon persists during voluntary contraction. Therefore, the purpose of this study was to determine whether a conditioning SAS has different effect at rest and during voluntary contraction. TMS was delivered to the hot spot for left biceps on eleven subjects at rest and nine of the eleven subjects during left elbow isometric flexion with and without conditioning SAS. TMS-induced MEP, TMS-induced force and silent period were used to determine the effect of conditioning SAS. In consistency with previous findings, TMS-induced MEP was smaller with a conditioning SAS (0.49 mV ± 0.37 mV) compared to no conditioning SAS (0.69 mV ± 0.52 mV) at rest. However, a conditioning SAS resulted in a significant shortening of the MEP silent period (187.22 ms ± 22.99 ms with SAS vs. 200.56 ms ± 29.71 ms without SAS) without any change in the amplitude of MEP (1.37 mV ± 0.9 mV with SAS V.S. 1.32 mV ± 0.92 mV without SAS) and TMS-induced force (3.11 N-m ± 2.03 N-m with SAS V.S. 3.62 N-m ± 1.33 N-m without SAS) during voluntary contraction tasks. Our results provide novel evidence that conditioning SAS has different effects on the motor cortex excitability during voluntary contraction compared with at rest.